Effects of External Magnetic Field on Focusing and Energy Distribution of Primary Electrons in an Ion Source - A. Yahya, Khalid; A. Hussein, Oday (Al-Nahrain Journal of Science, 2024)
The effect of the applied voltage and magnetic field on the defining slot in focusing and energy distribution of the primary filament electron beam was studied theoretically. In this work, SIMION 8.1 software was used to determine the best operational conditions for focusing and the distribution of the electron beam in the ion source system. Furthermore, the Larmor radius on the slot was calculated in two dimensions for different values of magnetic flux density. The results showed that the values of flux density and slot voltage play an effective role in improving the dimensions of beam spot and energy distribution in the source. The dimensions of beam spot were reduced by about 71% at voltage value of slot 75 volt and flux density 780 G. In addition; the kinetic energy distribution for electrons were computed at different magnetic flux and obtaining a homogeneous beam energy. The results of this research support the calculations of plasma source designers.